Weak nystagmus in the dark persists for months after acute unilateral vestibular loss - Chen, Chih-Chung; Bery, Anand K.; Chang, Tzu-Pu (Frontiers in Neurology, 2023)
Background Weak nystagmus with fixation removed can be seen both in normal individuals and in recovery from a unilateral vestibular insult, thus its clinical significance is unclear in patients with dizziness. We thus sought to compare features of nystagmus at various stages following unilateral vestibular loss (UVL). Methods We enrolled thirty consecutive patients after acute UVL with impaired vestibulo-ocular reflex (VOR) gain. The patients were allocated into three groups according to time from onset of symptoms: acute (1–7 days), subacute (8–30 days), and chronic (>30 days). Patients underwent video-oculography (with and without fixation) and video head impulse testing (vHIT) to determine VOR gain. We examined the relationships amongst SPV, VOR gain, and time from symptom onset across groups. Results There were 11, 10, and 9 patients in the acute, subacute, and chronic stages of UVL, respectively. With visual fixation, only 8 patients (26.7%) demonstrated nystagmus, all from the acute group. With fixation removed, 26 patients (86.7%) exhibited spontaneous nystagmus, including 90.9%, 90%, and 77.8% of the patients from the acute, subacute, and chronic groups, respectively. Horizontal nystagmus was paralytic (i.e., fast phase contralesional) in 25 (96.7%) cases. Horizontal SPV was negatively correlated with logarithm of time from onset to examination (r = −0.48, p = 0.007) and weakly negatively correlated with ipsilesional VOR gain (r = −0.325, p = 0.08). Conclusion In the subacute or chronic stages of UVL, paralytic nystagmus with fixation removed persisted at a low intensity. Therefore, weak nystagmus in the dark may have diagnostic value in chronic dizziness.